COMMUNITY SERVICE ACTIVITY TO HOUSEWIFE GROUP IN KAMPUNG LADANG BAMBU, MEDAN TUNTUNGAN - Ayu, Putri Chandra (Journal of Saintech Transfer, 2020)
Purple sweet potato is one of the agricultural products that has several advantages such as attractive color, high content of antioxidant, fiber and carbohydrate compounds and has a low glycemic index value. However, similar to the other agricultural products, the availability of purple sweet potatoes is seasonal, perishable, moldy and rotten. Proper processing with equipment or simple expertise can increase the economic value of purple sweet potato, so that it can be done by any group of people from either upper, middle or bottom. The purpose of this community service activities was to provide the technical guidance on processing the purple sweet potato into food products, namely noodles and sponge to open new business opportunities for group of housewives in the area of ​​community service partners namely Kampung Ladang Bambu, Medan Tuntungan. The expected outcome of this community service activity is the formation of a new business by a group of housewives to be able to increase the community income in Ladang Bambu Village, Medan Tuntungan. Keyword:, noodle, purple sweet potato, sponge